Intermittent Fasting Confers Protection in CNS Autoimmunity by Altering the Gut Microbiota - Cignarella, Francesca; Cantoni, Claudia; Ghezzi, Laura; Salter, Amber; Dorsett, Yair; Chen, Lei; Phillips, Daniel; Weinstock, George M.; Fontana, Luigi; Cross, Anne H.; Zhou, Yanjiao; Piccio, Laura (Cell metabolism, 2018)
Multiple sclerosis (MS) is more common in western countries with diet being a potential contributing factor. Here we show that intermittent fasting (IF) ameliorated clinical course and pathology of the MS model, experimental autoimmune encephalomyelitis (EAE). IF led to increased gut bacteria richness, enrichment of the Lactobacillaceae, Bacteroidaceae, and Prevotellaceae families and enhanced antioxidative microbial metabolic pathways. IF altered T cells in the gut with a reduction of IL-17 producing T cells and an increase in regulatory T cells. Fecal microbiome transplantation from mice on IF ameliorated EAE in immunized recipient mice on a normal diet, suggesting that IF effects are at least partially mediated by the gut flora. In a pilot clinical trial in MS patients, intermittent energy restriction altered blood adipokines and the gut flora resembling protective changes observed in mice. In conclusion, IF has potent immunomodulatory effects that are at least partially mediated by the gut microbiome. [Display omitted] •IF ameliorates the clinical course and pathology of the MS mouse model (EAE)•IF increases gut microbial diversity, alters their composition and metabolic pathways•Gut microbiota transfer from mice on IF led to protection from EAE in recipient mice•Findings with IER in MS patients partially recapitulates what is observed with IF in EAE Intermittent fasting confers protection in the multiple sclerosis animal model through effects on the gut microbiota; similar changes to the gut microbiota were observed in relapsing multiple sclerosis patients undergoing intermittent energy restriction.